Redefining Debt-to-Health, a triple-win health financing instrument in global health - Yunxuan Hu; Zhebin Wang; Shuduo Zhou; Jian Yang; Ying Chen; Yumeng Wang; Ming Xu (BMC, 2024)
Abstract Background As a recognized win-win-win approach to international debt relief, Debt-to-Health(D2H)has successfully translated debt repayments into investments in health-related projects. Although D2H has experienced modifications and periodic suspension, it has been playing an increasingly important role in resource mobilization in public health, particularly for low-and middle-income countries deep in debt. Main text D2H, as a practical health financing instrument, is not fully evidenced and gauged by academic literature though. We employed a five-step scoping review methodology. After posing questions, we conducted comprehensive literature searches across three databases and one official website to identify relevant studies.We also supplemented our research with expert interviews. Through this review and interviews, we were able to define the concept and structure of D2H, identify stakeholders, and assess its current shortcomings. Finally, we proposed relevant countermeasures and suggestions. Conclusion This paper examines the D2H project's implementation structure and influencing variables, as well as the current research plan's limitations, with a focus on the role health funding institutions have played during the project's whole life. Simultaneously, it examines the interdependencies between debtor nations, creditor nations, and health financing establishments, establishing the groundwork for augmenting and revamping D2H within the ever-changing worldwide context of health development assistance.